Management of Systemic Lupus Erythematosus with Lupus Nephritis and Subclinical Hypothyroidism: a Case Report - Basuki, Tedo Briantono; Awalia, Awalia (Journal of Neonatal Surgery, 2025)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease characterized by diverse clinical manifestations affecting multiple organ systems, often complicating diagnosis and management. Lupus nephritis (LN) and thyroid dysfunction, notably subclinical hypothyroidism, are common comorbidities that influence disease outcomes. We report the case of a 29-year-old female diagnosed with SLE presenting lupus nephritis and subclinical hypothyroidism. Clinical features included joint pain, edema, hair loss, and foamy urine, supported by laboratory findings of thrombocytopenia, proteinuria, and elevated thyroid-stimulating hormone (TSH). Management involved corticosteroids, hydroxychloroquine, mycophenolate mofetil, and levothyroxine replacement therapy. Despite ongoing immunosuppressive treatment, persistent proteinuria highlighted challenges in disease management. Regular monitoring of renal and thyroid function is crucial to reduce morbidity and mortality.